(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, today’s global changes, the daily development of science and technology and information and communication technologies require pedagogical skill, sharp will, pedagogical-psychological knowledge, deep knowledge of one’s subject and high thinking, political taking into account the fact that it requires literacy, a wide and thoughtful range of thinking, it is important to talk about the pedagogical skill and its components, which are considered extremely necessary for every teacher in the field of pedagogical sciences.